A Study on Impact of COVID-19 on the Nutrition and Exercise Regime of Lifestyle Disorder Patients (Non-Communicable Disease) - Sheetal Mahendher; Shantanu Paul; Anshitha Sharma; Leonard L (Sumatera Medical Journal, 2024)
Background: The COVID-19 pandemic has significantly altered people's eating and activity habits all around the world. Lockdowns and social isolation policies have altered daily routines, changed people's levels of physical activity, and changed how they eat. Objective: The goal of this study is to fill in the knowledge gaps regarding the effects of COVID-19 on people who have lifestyle disorders by studying the variations in exercise routines and the necessary nutrition intake during and after the lockdown. Methods: In order to gather information from people with NCDs, the study used a mixed-methods approach that combines a questionnaire survey and focused discussion. Results: The study offers insights into how people with lifestyle disorders alter their exercise regimens, exercise style, and adherence to nutritional diets. The findings show that the pandemic has driven people to change their workout routines, moving away from gyms and outside activities toward alternate at-home techniques. Conclusion: The study also emphasizes the difficulties people encountered in sticking to rigorous nutritional diets during the epidemic because of the restricted availability of fresh and nourishing foods. It further highlights the significance of consistent exercise and mindful eating for those with lifestyle disorders, particularly during times of crisis.